Category Shift in the Translation of the Novel the Alchemist by Paulo Coelho - Syahputri, Diani; Wulan, Yuli (English Teaching and Linguistics Journal (ETLiJ), 2025)
This research investigates category shifts in the Indonesian translation of Paulo Coelho's novel "The Alchemist." The study addresses translation inadequacies that potentially affect reader comprehension and examines the strategic implementation of category shifts. Research objectives include identifying types of category shifts, determining their distributional frequency, and analyzing the predominance of specific shift types. The study employs descriptive qualitative methodology with document analysis techniques, examining data from the initial and final twenty pages of the novel. The analysis identifies four category shift types with the following distribution: unit shift (40%), structure shift (31%), class shift (19%), and intra-system shift (10%). These findings contradict Catford's (1965) theoretical assertion that structure shifts predominate in translation processes. The prevalence of unit shift reflects fundamental lexical disparities between English and Indonesian linguistic systems, where semantic equivalence frequently necessitates morphological expansion or reduction. Translators demonstrate a preference for unit shifts due to their capacity to preserve naturalness in the target language without extensive syntactic restructuring. This phenomenon suggests that lexical considerations supersede grammatical constraints in translation decisions between typologically distinct languages. The dominance of unit shift indicates translational prioritization of communicative effectiveness through pragmatic lexical adjustments rather than strict structural correspondence.